Analisis Pengaruh Penggunaan Media Sosial Terhadap Manajemen Waktu Belajar Mahasiswa PGSD - anisah nur afliyani; Attasya Fadila Efendi; Jesi Alexander Alim; Mitha Dwi Anggriani (Jurnal Mahasiswa: Jurnal Ilmiah Penalaran dan Penelitian Mahasiswa, 2025)
This study aims to analyze the influence of social media use on the study time management of PGSD students at the Faculty of Teacher Training and Education, University of Riau. The background of this study is the phenomenon of increasing intensity of social media use among students, which has the potential to affect learning effectiveness. This study uses a quantitative method with a survey approach, where data is collected by distributing Likert-scale questionnaires to student respondents. The survey approach was chosen because it can describe the real conditions of students directly based on their answers, so the results obtained are more representative. The results show that the level of social media use is in the moderate category, while students' study time management skills are in the fairly good category. These findings indicate that although students actively use social media, they are still able to manage their time effectively so that the negative impacts of social media can be minimized. This study contributes by confirming that the key factor in maintaining learning effectiveness in the digital era lies not in the frequency of social media use, but in students' discipline and time management skills. Thus, the results of this study enrich the understanding of the role of time management as a balance between social media use and academic activities.